The Electrocardiogram in the Differential Diagnosis of Cardiologic Conditions Related to the COVID-19 Pandemic - Predabon, Bruna; Souza, Arthur Zanfrilli Marques; Sumnienski Bertoldi, Gustavo Henrique; Sales, Rafaela Louise; Luciano, Karila Scarduelli; Ronsoni, Rafael de March (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
The World Health Organization (WHO) declared Sars-CoV infection and COVID-19 as a pandemic and global emergency. In addition to viral pneumonia and the severe acute respiratory syndrome (Sars), the heart is affected in some patients due to the detection of biomarkers and reported cases of myocarditis and pericarditis. Therefore, the knowledge of electrocardiogram presentation of these actual infections can guide the choice for the best treatment and can help to reduce misdiagnosis, mainly the acute myocardial infarction, which is the main differential diagnosis.